The Effect of Accounting Information, Profitability and Leverage on Stock Prices in Companies Listed on the Indonesia Stock Exchange - Rosalia, Vema; Rahayu, Sri; Arum, Enggar Diah Puspa; Wiralestari, Wiralestari (Formosa Journal of Multidisciplinary Research, 2025)
For the purpose of this research, we will look at stocks traded on the Indonesia Stock Exchange and analyze their performance relative to certain financial metrics, including EPS, PBV, NPM, ROA, ROE, and DER. Using secondary data collected from the Indonesia Stock Exchange, this research employs a quantitative approach. Organizations trading on the Indonesia Stock Exchange that are involved in healthcare are the focus of this study. Using Purposive Sampling, 45 companies were selected for the study sample that covers the years 2021–2023. The statistical package for the social sciences (SPSS) 26 was used for data analysis in this research. Study findings show that EPS has a significant impact on stock prices, but NPM, ROA, ROE, DER, and price-to-book value (PBV) do not. On the other hand, EPS, NPM, ROA, ROE, and DER all have an effect on stock prices, and they are significant.